Hubungan Penerimaan Insentif Finansial Dan Interpersonal Antar Perawat Dengan Kinerja Perawat Di RSU Al-Fatah Ambon - Hasna Tunny (Journal Pharma Saintika, 2023)
Nurses are health workers who play an important role in health services. Nurses are required to be committed to carrying out their duties according to competence, but this is not balanced by what they get from the hospital, in this case in the form of incentives.Incentives are a means of motivation that encourages employees to work with optimal abilities, resulting in good performance. Apart from that, interpersonal relationships can also influence performance. Interpersonal relationships have an impact on workload due to less harmonious and emotional interactions between individuals in the environment which can have negative effects that trigger conflict at work. The aim of this research was to determine the relationship between receiving financial incentives and interpersonal between nurses and the performance of nurses at RSU Al-Fatah Ambon.Quantitative research using designCross Sectional. The total sample was 48 nurses in the inpatient room with the sampling technique, namely total sampling with the chi square statistical test. Value statistical test resultsFisher's Exact Testshows receipt of incentives p.value 0.024 <0.05 and interpersonal relationships p.value 0.002 <0.05. This shows that Ha is accepted, where there is a relationship between receiving incentives and nurse performance, and there is an interpersonal relationship with nurse performance at RSU Al-Fatah Ambon.